Correction to: Impact of antibiotic therapy on the development and response to treatment of immune checkpoint inhibitor-mediated diarrhea and colitis. Issue 1 (17th December 2019) - Abu-Sbeih, Hamzah; Herrera, Lauren Nicholas; Tang, Tenglong; Altan, Mehmet; Chaftari, Anne-Marie; Okhuysen, Pablo C.; Jenq, Robert R.; Wang, Yinghong
Abstract : Following publication of the original article [1], the authors have reported that an author's name has been incorrectly spelled: the correct given name is Anne-Marie (instead of Anne-Maria P) and family name is Chaftari.